Crises et conflits dans les territoires insulaires de la Caraïbe et de l’Océan Indien (2009-2010) - Michel Desse; Mario Sélise (Études Caribéennes)
Environmental crises have a profound impact on island economies and societies, and this so exacerbated in Haiti after the devastating earthquake of January 12, 2010. Small islands in the Caribbean and in the Indian Ocean endured numerous crises sometimes of local origin but more often due to external factors. Beyond the current global downturn, insularity and small size are factors that aggravate the economic crisis and increasing tensions in these areas. In DROM (Department Region Overseas), social movements have been very important.